2023
DOI: 10.1161/jaha.122.026891
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Atrial Remodeling in Heart Failure With Recovered Ejection Fraction

Abstract: Background Heart failure with recovered ejection fraction (HFrecEF) has been a newly recognized entity since 2020. However, the concept has primarily focused on left ventricular ejection fraction improvement, with less focus on the recovery of the left atrium. In this study, we investigated changes in left atrial (LA) echocardiographic indices in HFrecEF. Methods and Results An inpatient cohort with heart failure with reduced ejection fraction (HFrEF) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It is now known that not only left ventricular remodelling but also LA remodelling has prognostic significance. A recent publication suggests that an improved LVEF in HFrEF is associated with a higher rate of LA remodelling 37 . Further, LA remodelling, like left ventricular remodelling, predicts a better prognosis and lower mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now known that not only left ventricular remodelling but also LA remodelling has prognostic significance. A recent publication suggests that an improved LVEF in HFrEF is associated with a higher rate of LA remodelling 37 . Further, LA remodelling, like left ventricular remodelling, predicts a better prognosis and lower mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication suggests that an improved LVEF in HFrEF is associated with a higher rate of LA remodelling. 37 Further, LA remodelling, like left ventricular remodelling, predicts a better prognosis and lower mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, systolic [ 29 , 30 ] and diastolic [ 31 , 32 ] HF increase left atrial pressure. It has been recently shown that left atrial size is a good predictor of HF in human patients [ 33 ] . Atrial hypertrophy [ 9 , 28 , 34 ] and increased left atrial fibrosis [ 35 , 36 ] have been previously described in the cTAC model, but no analysis of atria structure or function has been reported so far in the mTAC model.…”
Section: Discussionmentioning
confidence: 99%
“…Even when these patients have improved clinical outcomes, they remain at risk for recurrent HF, especially if significant cardiac remodeling occurs before rhythm control is achieved [ 21 ]. However, those with left atrial reverse remodeling (about 60 %) have a better prognosis [ 22 ].…”
Section: Impact Of Af On Patients With Hfpefmentioning
confidence: 99%